KRITIK AL-MARAGHI ATAS PENDAPAT IGNAZ GOLDZIHER DALAM BUKU INTRODUCTION TO ISLAMIC THEOLOGY AND LAW (TAJDID: Jurnal Ilmu Ushuluddin, 2023)
This research is a form of criticism of Ignaz Goldziher's opinion in the book Introduction to Islamic Theology and Law which is considered to be at odds with the Sunnah and the word of God in the Qur'an which is the main reference source for Muslims. Ignaz's biggest mistake was to deny the sacredness of the Prophet as a messenger of God and consider the Prophet only as an ordinary human being in general which then gave birth to opinions that are subjective to Islam. Therefore, this research uses the method of character study and historical criticism analysis of Tafsir Al-Maraghi in refuting these opinions. Ignaz Goldziher's thinking in the book is influenced by the Historical Criticism approach he takes in studying Islam, so Ignaz often relates the teachings of Islam to the teachings of previous religions. Imam Maraghi rejects this information, that everything that God has revealed to the Prophet Muhammad in the form of Islamic teachings or the Word of God in the Qur'an is a form of guidance and guidance for humans to be saved from the world's misguidance.Penelitian ini merupakan bentuk kritik pendapat Ignaz Goldziher dalam buku Introduction to Islamic Theology and Law yang dinilai bersebrangan dengan Sunnah dan firman Allah didalam Al-Qur’an yang menjadi sumber rujukan utama umat Islam. kesalahan terbesar Ignaz yakni menafikan sakralitas Rasulullah sebagai utusan Allah dan menganggap Nabi hanya sebagai manusia biasa pada umumnya yang kemudian melahirkan pendapat-pendapat yang bersifar subjektif terhadap Islam. Oleh karena itu, peneilitian ini menggunakan metode studi tokoh dan analisis kritik historis Tafsir Al-Maraghi dalam membantah pendapat-pendapat tesebut. Pemikiraan Ignaz Goldziher didalam buku tersebut dipengaruhi oleh pendekatan Historical Criticism yang dilakukannya dalam mengkaji Islam, sehingga Ignaz sringkali mengaitkan ajaran Islam dengan ajaran agama-agama sebelumnya. Imam Maraghi menolak keterangan tersebut, bahwa segala sesuatu yang sudah Allah wahyukan kepada Nabi Muhammad baik berupa ajaran Islam atau Firman Allah dalam Al-Qur’an adalah bentuk petunjuk dan pedoman bagi manusia agar selamat dari kesesatan dunia.